(untitled) (International Journal of Language, Literacy and Translation, 2025)
Language is a prime vehicle for communication. As language is used for communication, there is the need to avoid certain linguistic items in order not to break communication. In daily communication, speakers use language that ensures good relationships with others to avoid embarrassment, misunderstanding and friction (Zhang & You, 2009). This helps save one’s face in communication (Goffman, 1955). Many contemporary Ghanaian music feature subjects that demand the use of words that the Ghanaian culture disallows to be rendered in plain language. Many of these are words related to sexual relationship. To avoid face threatening, artists employ various avoidance strategies such as the use of homophones, metaphor, pronouns and ideophones. This paper takes a look at the works of two afro pop artists; Wendy Shay and Ebony Reigns to see how they employ indirectness to communicate explicit sexual content. In the analysis, the SPEAKING Theory by Hymes (1974) is applied. We show that, the artists are successful with the use of indirectness to conceal the unmentionables in Akan. However, the intent of the artists in communicating sexual content to the listener is clearly expressed through gestures. We conclude that, communicating sexual content through gestures is easier than to communicate same using words or language.